Več športa, manj zaslona - Bon, Marta (Pravnik, 2025)
In 2024, the City of Ljubljana, through its Department of Sport, published More Sports, Less Screens: Recommendations for Screen Use Among Young Athletes. This manual is the result of a collaborative effort between sports professionals, City of Ljubljana staff, and experts from the Logout Institute. Over ten contributors authored the content, with additional input from renowned athletes and coaches who participated in focus groups. The introduction outlines scientific research on the negative impacts of screen use on mental health. The main section offers practical recommendations across various areas, including screen time and space guidelines in sports clubs, promoting dignity and mutual respect, supporting mental health, safeguarding privacy, managing media exposure, and responding to peer violence. Each recommendation is presented from the perspective of the athlete, coach, and parent, emphasising the importance of maintaining respectful and supportive relationships in all aspects of screen use.
Keywords: duševno zdravje; habits; Knjižne recenzije; mental health; mladi; Mladi športniki; navade; screen use; sports; Šport; uporaba zaslonov; youth